Characterising polypharmacy in the very old: Findings from the Newcastle 85+ Study. - Laurie E Davies; Andrew Kingston; Adam Todd; Barbara Hanratty (PLoS ONE)
Background Polypharmacy is potentially harmful and under-researched amongst the fastest growing subpopulation, the very old (aged ≥85). We aimed to characterise polypharmacy using data from the Newcastle 85+ Study-a prospective cohort of people born in 1921 who turned 85 in 2006 (n = 845). Methods The prevalence of polypharmacy at baseline (mean age 85.5) was examined using cut-points of 0, 1, 2-4, 5-9 and ≥10 medicines-so-called 'no polypharmacy', 'monotherapy', 'minor polypharmacy', 'polypharmacy' and 'hyperpolypharmacy.' Cross-tabulations and upset plots identified the most frequently prescribed medicines and medication combinations within these categories. Mixed-effects models assessed whether gender and socioeconomic position were associated with prescribing changes over time (mean age 85.5-90.5). Participant characteristics were examined through descriptive statistics. Results Complex multimorbidity (44.4%, 344/775) was widespread but hyperpolypharmacy was not (16.0%, 135/845). The median medication count was six (interquartile range 4-8). Preventative medicines were common to all polypharmacy categories, and prescribing regimens were diverse. Nitrates and oral anticoagulants were more frequently prescribed for men, whereas bisphosphonates, non-opioid analgesics and antidepressants were more common in women. Cardiovascular medicines, including loop diuretics, tended to be more frequently prescribed for socioeconomically disadvantaged people (<25th centile Index of Multiple Deprivation (IMD)), despite no difference in the prevalence of cardiovascular disease (p = 0.56) and diabetes (p = 0.92) by IMD. Conclusion Considering their complex medical conditions, prescribing is relatively conservative amongst 85-year-olds living in North East England. Prescribing shows significant gender and selected socioeconomic differences. More support for managing preventative medicines, of uncertain benefit, might be helpful in this population.